Gender Categorization Is Abnormal in Cochlear Implant Users - Fuller, Christina D. (J Assoc Res Otolaryngol, 2014)
In normal hearing (NH), the perception of the gender of a speaker is strongly affected by two anatomically related vocal characteristics: the fundamental frequency (F0), related to vocal pitch, and the vocal tract length (VTL), related to the height of the speaker. Previous studies on gender categorization in cochlear implant (CI) users found that performance was variable, with few CI users performing at the level of NH listeners. Data collected with recorded speech produced by multiple talkers suggests that CI users might rely more on F0 and less on VTL than NH listeners. However, because VTL cannot be accurately estimated from recordings, it is difficult to know how VTL contributes to gender categorization. In the present study, speech was synthesized to systematically vary F0, VTL, or both. Gender categorization was measured in CI users, as well as in NH participants listening to unprocessed (only synthesized) and vocoded (and synthesized) speech. Perceptual weights for F0 and VTL were derived from the performance data. With unprocessed speech, NH listeners used both cues (normalized perceptual weight: F0 = 3.76, VTL = 5.56). With vocoded speech, NH listeners still made use of both cues but less efficiently (normalized perceptual weight: F0 = 1.68, VTL = 0.63). CI users relied almost exclusively on F0 while VTL perception was profoundly impaired (normalized perceptual weight: F0 = 6.88, VTL = 0.59). As a result, CI users’ gender categorization was abnormal compared to NH listeners. Future CI signal processing should aim to improve the transmission of both F0 cues and VTL cues, as a normal gender categorization may benefit speech understanding in competing talker situations.